2008
DOI: 10.1016/j.neuroscience.2008.08.060
|View full text |Cite
|
Sign up to set email alerts
|

A novel electrophysiological model of chemotherapy-induced cognitive impairments in mice

Abstract: Purpose-Chemotherapeutic agents are known to produce persistent cognitive deficits in cancer patients. However, little progress has been made in developing animal models to explore underlying mechanisms and potential therapeutic interventions. We report an electrophysiological model of chemotherapy-induced cognitive deficits using a sensory gating paradigm, to correspond with performance in two behavioral tasks.Experimental Design-Mice received four weekly injections of methotrexate and 5-fluorouracil. Whole-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 49 publications
4
34
1
1
Order By: Relevance
“…Similarly, patients receiving adjuvant chemotherapy (which includes 5FU in the regime) for cancer experience impairments in verbal and visual memory, processing speed, concentration and attention (de Ruiter et al 2011;Vardy and Tannock 2007). In contrast, Gandal et al (2008) failed to find impairments in NOR or fear conditioning in mice treated with combined 5FU and MTX, while inexplicably, Lee et al (2006) found transient improvements in spatial MWM and Stone maze performance in rats treated with 5FU alone, which then disappeared with later testing. However, these results may be explained by differences in experimental design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, patients receiving adjuvant chemotherapy (which includes 5FU in the regime) for cancer experience impairments in verbal and visual memory, processing speed, concentration and attention (de Ruiter et al 2011;Vardy and Tannock 2007). In contrast, Gandal et al (2008) failed to find impairments in NOR or fear conditioning in mice treated with combined 5FU and MTX, while inexplicably, Lee et al (2006) found transient improvements in spatial MWM and Stone maze performance in rats treated with 5FU alone, which then disappeared with later testing. However, these results may be explained by differences in experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results may be explained by differences in experimental design. For example, Gandal et al (2008) employed a 24-h delay between NOR sample and test trials, while a maximum of 2 h separated the sample and test trials in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to behavior, one measures the exact same phenomenon across species and no interpretations of “meaning or intent” are required. Many studies have demonstrated that both mouse and human ERP components are similarly affected by certain pharmacological treatments and stimulus manipulations [6163]. Thus, recording EEG and ERPs in preclinical studies provides the most translational model system for physiological deficits associated with psychosis.…”
Section: Measurementsmentioning
confidence: 99%
“…In mice the P1, P2, P3, and N1 peaks are equivalent in stimulus and pharmacological response properties to human peaks P50, P200, P300, and N100, respectively, when using auditory ERPs, described by Connolly and collaborators (2004). In an effort to establish an electrophysiological model of chemotherapy-induced cognitive impairment, Gandal and colleagues (2008) studied the effect of chronic regimens of methotrexate or 5-fluorouracil in mice using an auditory ERP paradigm (Gandal et al 2008). Chemotherapy-treated mice showed a significant impairment in sensory gating as evidenced by an increased response ratio between P1 and N1 amplitudes following presentation of auditory stimuli.…”
Section: Evoked and Event-related Potentialsmentioning
confidence: 99%